2017
DOI: 10.1515/prilozi-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

BDI in the Assessment of Depression in Different Medical Conditions

Abstract: As a common disorder, depression must be diagnosed not only in psychiatric but also in different medical settings, especially in patients with chronic diseases. Beck Depression Inventory is valuable and sensitive self-report inventory used worldwide for assessment depressive symptoms. In this research we present obtained scores of BDI in different group of disorders and we showed that BDI scores are related to the clinical condition, as well as with the age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…BDI-II follows the criteria for depression listed in the fourth edition of the DSM. The test consists of twenty-one questions that not only assess the presence of depression, but also the severity of depression as well [31] . Each question has a set of at least four possible responses ranging in intensity, with a value of 0 to 3 is assigned for each answer and the total score compared to a key to determine severity.…”
Section: Depressionmentioning
confidence: 99%
“…BDI-II follows the criteria for depression listed in the fourth edition of the DSM. The test consists of twenty-one questions that not only assess the presence of depression, but also the severity of depression as well [31] . Each question has a set of at least four possible responses ranging in intensity, with a value of 0 to 3 is assigned for each answer and the total score compared to a key to determine severity.…”
Section: Depressionmentioning
confidence: 99%
“…IIEF is a widely used multi-dimensional self-reported questionnaire for the evaluation of male sexual function and has been regarded as the gold-standard treatment outcome measurement for erectile dysfunction (Rosen et al, 2002). BDI is widely used self-reported questionnaire that evaluates the degree of depressive symptoms and it has been proven to have both reliability and sensitivity (Pop-Jordanova, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The average in western Germany was 9.2 percent, and in Edmonton in Canada, it was reported at 9.6 percent 1 . An international research by the WHO, reported the prevalence of major depression in the general population to be from 1 percent in the Czech Republic to 16.9 percent in the United States, with an average of 8.3 percent in Canada, and up to 9 percent in Chile 1 . The average global prevalence of depression is reported to be about 15 percent 4 .…”
Section: Introductionmentioning
confidence: 93%